O movimento social contra o aterro sanitário em Marituba (PA): um estudo sobre o fórum permanente ‘fora lixão’ - MORAES, Fabrício Tavares de (Universidade Federal do Pará, 2023)
This study makes an analysis of the social movement called Permanent Forum 'Fora Lixão' in its practices in the city of Marituba (PA) under the conception of the Theory of Political Confrontation (TPP). The research resorted to a qualitative approach and the case study method, following the procedures of interviews, journalistic, judicial, administrative documents and bibliographical research. The results demonstrated an internal organization of the movement composed of community associations, political parties, social movements and segments of the Catholic Church, as well as forms of popular participation that oscillated between confrontation and collaboration with the State. The research informs us about how organized civil society and public institutions-built arrangements, partnerships and forms of political participation, in the case of the rejection of the Marituba landfill, popularly known as “Marituba dump”. The research also informs about the strengthening of popular mobilization, in order to conquer a popular participatory democracy, for the treatment of solid waste in the Metropolitan Region of Belém, according to more evolved technical parameters and consistent with the guidelines of the National Waste Policy Solids and the laws that support it.